UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI ZAKAT DENGAN MENGGUNAKAN METODE TEAM QUIZ PADA KELAS X MIA 2 SMA NEGERI 1 KEPENUHAN - Makmur Makmur (JURNAL PENDIDIKAN ROKANIA, 2021)
This study discusses efforts to improve fiqh learning outcomes, the subject matter of zakat in class X MIA 2 SMA Negeri 1 Kecepatan for the 2019/2020 school year. This research is motivated by the phenomenon of low learning outcomes which are marked by the lack of students who are able to exceed the KKM score. In this study, the use of the team quiz method in learning fiqh, the subject matter of zakat, is offered. The formulation of the problem put forward is "Can the team quiz method improve zakat learning outcomes for class X MIA 2 SMA Negeri 1Full for the 2019/2020 school year? These problems were studied using the method of classroom action research (classroom action research). The data collection method uses documentation, observation, and test techniques. Based on the results of the study, it was concluded that the demonstration method with the team quiz method could improve the fiqh learning outcomes of the subject matter of zakat in class X MIA 2 SMA Negeri 1 Kecepatan for the 20192020 school year. The data obtained showed that in the pre-cycle the average value of the class was 51.42, in cycle 1 it increased again to 72, and in the cycle it rose to 79. The classical completeness data in cycle 1 was 28.57%, in cycle 1 it was 71.43%, and increased again in cycle 2 to 88.57%